Utilization strategies for deep coal-measure reservoirs with different stacking patterns in Linxing block, Ordos Basin - Lichun SUN; Jia LIU; Xinze LI; Le SUN; Maojun FANG; Na LI; Weipeng FAN (Shiyou shiyan dizhi)
The Linxing block in the Ordos Basin has entered the stage of co-production of tight gas and coalbed methane (CBM), and the stacking patterns of tight sandstone and coal seams directly affect the production methods. By analyzing the stacking relationships and production dynamics using different development methods in the Linxing block, the utilization strategies for deep coal-measure reservoirs were investigated. Based on the sedimentary characteristics and relative spatial positions of tight sandstone and coal seams, the sand-coal stacking patterns in the Linxing block were mainly categorized into interbedded sand-coal type and upper sand-lower coal type. By comparing the development status under different stacking patterns, it was found that horizontal wells were preferred for the independent development of deep CBM, and wells co-producing CBM and tight gas had higher initial gas production capacity than vertical or directional wells producing CBM alone. An optimization chart of deep coal-measure reservoir utilization strategies under different stacking patterns was further established, with economic efficiency as the optimization objective. When CBM abundance is less than 1.1×108 m3/km2 and the tight gas reservoir is classified as a Class Ⅰ or Class Ⅱ, a co-production approach should be adopted. Under the condition that CBM abundance ranges from 1.1×108 to 1.5×108 m3/km2, if the tight gas reservoir is underdeveloped, horizontal wells should be used for the independent utilization of CBM; if the tight gas reservoir is classified as Class Ⅰ or Ⅱ, a co-production method should be adopted. Under the condition that CBM abundance exceeds 1.5×108 m3/km2, if the tight gas reservoir is underdeveloped or classified as Class Ⅱ or Ⅲ, horizontal wells should be used to develop the coal seams solely; if the tight gas reservoir is classified as Class Ⅰ, tight gas and CBM should be developed separately. The research provides technical support for the efficient co-production of deep CBM resources in the Linxing block and other similar blocks.